Omega-3 fatty acid ethyl esters improve low-density lipoprotein subclasses without increasing low-density lipoprotein-cholesterol levels: A phase 4, randomized study. (January 2020) - Masuda, Daisaku; Miyata, Yuko; Matsui, Shingo; Yamashita, Shizuya
Abstract: Background and aims: We aimed to investigate blood lipid and lipoprotein profiles in patients with dyslipidemia receiving hydroxymethylglutaryl-coenzyme A reductase inhibitors (statins) after 8 weeks of omega-3 fatty acid ethyl esters (Omega-3) treatment, using high-performance liquid chromatography with highly-sensitive gel filtration columns. Methods: In this phase 4, randomized, open-label study, patients with dyslipidemia receiving statins were randomized 1:1 to Omega-3 treatment (oral Omega-3 2 g twice daily) or Control (no Omega-3). Primary endpoint was change in mean particle size of low-density lipoprotein (LDL) and small dense LDL (cholesterol monitoring) in the specific 20-lipoprotein fraction assay. Secondary endpoints included changes in lipids, apolipoproteins, and lipoprotein concentrations in fasting blood. Changes were compared between treatments using analysis of covariance, adjusted by baseline fasting triglycerides and age. Results: Fifty-three patients were randomized (Omega-3, n = 24; Control, n = 29). The difference in LDL particle size between Omega-3 and Control groups was significant at week 8 ( p  = 0.0040). Differences in least squares mean change in concentration from baseline to week 8 between Omega-3 and Control groups were significant for total cholesterol ( p  = 0.0009), LDL-C ( p  = 0.0442), non-high-density lipoprotein cholesterol ( p  = 0.0009), and remnant lipoprotein-cholesterol ( p  = 0.0396). Differences were significant for apolipoproteins AI, AII, B, B-48, B-100, CII, CIII, and CII/III, but not apolipoprotein E. Conclusions: Significant increases in LDL particle sizes and significant decreases in blood lipid, lipoprotein and apolipoprotein concentrations were observed with Omega-3 compared with Control. Omega-3 may improve blood lipid profile and increase LDL particle size, resulting in an anti-atherogenic profile. Graphical abstract: Image 1 Highlights: Dyslipidemia patients received omega-3 fatty acid ethyl esters or no treatment. Low-density lipoprotein (LDL) particle sizes increased in treated patients. Blood lipid concentrations decreased in treated patients. Lipoprotein and apolipoprotein concentrations decreased in treated patients. Serum lipid profile and LDL particle size may improve in treated patients.